2006
DOI: 10.1162/jeea.2006.4.2-3.594
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing and Offshoring of Business Services: How Important is Ict?

Abstract: This paper considers the impact that information and communication technology (ICT) has on firms' choices over organisational form. In particular, the decision over whether to produce in-house or outsource services, and the decision over the location of activity. ICT reduces the transaction and adjustment costs of moving activity outside the firm, and of carrying it out at greater geographic distance. We find that more ICT-intensive firms purchase a greater amount of services on the market and they are more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
76
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 12 publications
2
76
2
1
Order By: Relevance
“…Outsourcing is also related to technology: it seems that there is a positive relation between KIBS outsourcing and investments in computer equipment and Information and Communication Technology (ICT). For instance, Abramovsky and Griffith (2006) find that ICT stimulates outsourcing by reducing the costs of moving activity outside the firms. Finally, ICT can be relevant to KIBS in other ways.…”
Section: Introductionmentioning
confidence: 99%
“…Outsourcing is also related to technology: it seems that there is a positive relation between KIBS outsourcing and investments in computer equipment and Information and Communication Technology (ICT). For instance, Abramovsky and Griffith (2006) find that ICT stimulates outsourcing by reducing the costs of moving activity outside the firms. Finally, ICT can be relevant to KIBS in other ways.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the empirical literature on ICT and growth, the firms that invest more in ICT and make complementary changes to their internal organization, as implied by the off-shoring of business activities previously performed in house, are more productive (Brynjolfsson and Hitt 2000;Bresnahan et al 2002;Bloom et al 2007). Moreover, Abramovsky and Griffith (2006) found that more ICT intensive firms purchased a greater amount of services in the market and they were more likely to purchase off-shore than less ICT intensive firms. Therefore ICT intensive firms should be better able to benefit from service off-shoring because of the way in which ICT eases business interactions (Brynjolfsson andHitt 2000, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The increasing role of offshoring has been favoured by the interplay between three factors: advances in technology, economic and competitive pressures to reduce costs and improve productivity, and institutional developments favouring trade liberalisation. In particular, the progress in Information and Communication Technologies (ICT) facilitated the tradability of services so that one of the most significant changes in economic activity over recent years has been the substantial growth of service off-shoring (Abramovsky and Griffith 2006;. So far, most of existing empirical evidence on the economic impact of international outsourcing has been primarily focused on its potentially negative effects on domestic employment (Feenstra and Hanson 1996;Olsen 2006;Blinder 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Abramovsky and Griffith () find that establishments using the Internet outsource approximately 10.6% more business services than those that do not in the UK, while Tomiura () shows evidence suggesting that firms connected with computer networks tend to outsource some of their manufacturing tasks in Japan.…”
mentioning
confidence: 99%
“…Following the previous literature, we define “outsourcing” (“offshoring”) as the procurement of inputs via domestic outsourcing or foreign outsourcing (via foreign outsourcing or FDI). For example, Abramovsky and Griffith (, p. 595) define them as follows: “Outsourcing is the decision to make or buy, regardless of where the activity takes place. … Offshoring is about where the activity takes place, regardless of whether it is within the corporate boundary or outside it”.…”
mentioning
confidence: 99%